Brief Report: Long-term Outcomes and Their Determinants in Patients on Antiretroviral Treatment in Ethiopia, 2005/6–2011/12. (1st December 2015) - Assefa, Yibeltal; Lynen, Lut; Kloos, Helmut; Hill, Peter; Rasschaert, Freya; Hailemariam, Damen; Neilsen, Graham; Van Damme, Wim
Abstract : Background: Antiretroviral treatment (ART) programs in many resource-limited settings have expanded treatment toward universal access. Ethiopia is one of the countries that has been scaling up ART toward universal access, but with very few data on long-term outcomes and their determinants. The objective of this study was to identify the level of long-term outcomes and their determinants in patients on ART in Ethiopia. Methods: A retrospective cohort study was conducted in 3 health facilities (2 hospitals and 1 health center) between July and September, 2014. Loss to follow-up, death, attrition, and retention were the primary outcomes. Data were collected from patient registers and medical records for the period 2005/6–2011/12. Results: A total of 11, 731 patients were included in the study. The overall retention rate was 78 per 100 person-months. Retention rates were 82%, 74%, and 72% at 24, 60, and 84 months on ART, respectively. Retention was associated with male sex, adolescent age, marital status, advanced HIV disease, illiteracy, and peer-support services; however, long-term retention was associated independently with only male sex [with adjusted hazard ratio (aHR) 0.68 (0.56 to 0.77)], married patients [with aHR 0.62 (0.54 to 0.72)], and peer-support services [with aHR 1.62 (1.58 to 1.66)]. Discussion and Conclusions: ART programs have lost most of their patients during the first 24 months on ART. It is, therefore, imperative that HIV/ART programs ensure people are tested, linked to care, and initiated on ART early. ART programs should also design and implement interventions, including peer-support services, which are targeted to male, adolescent, unmarried, and illiterate patients.